The Role of Motivation, Ethics and Satisfaction on Performance (A Study in Kragilan Subdistrict, Serang Regency) - Ratu yeti darmayanti; Rigwan Rigwan; Masoca Hezra Pramana; Sholeh Hidayat; Dian Wirtadipura (CV. Era Digital Nusantara, 2026)
This study aims to analyze the effect of work motivation, work ethic, and job satisfaction on employee performance at the Kragilan District Office, Serang Regency. This research employed a quantitative approach with an ex post facto design. Data were collected through questionnaires distributed to all employees, totaling 60 respondents, using a census sampling technique. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results show that work motivation, work ethic, and job satisfaction have a positive and significant effect on employee performance. Among these variables, job satisfaction has the most dominant effect on employee performance. Simultaneously, the three variables significantly contribute to explaining variations in employee performance. The findings indicate that improving employee performance in public sector organizations can be achieved through enhancing work motivation, strengthening work ethic, and increasing job satisfaction. This study contributes empirically to the development of human resource management, particularly in improving employee performance in government institutions.